Implications of Colombia’s Entry into the OECD - Vallejo Zamudio, Luis E. (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The Organization for Economic Cooperation and Development (OECD) emerged in the post-war period from the initiative of European leaders, who considered that to achieve a lasting peace the best thing was to “encourage cooperation and recovery, instead of punishing the vanquished”.